EFFECT OF AQUEOUS EXTRACT OF Ipomoea staphylina ON INDIAN EARTHWORM - GHOSH, SOUMYADEEP; FIRDOUS, SM (Asian Journal of Pharmaceutical and Clinical Research, 2014)
Objective: Aqueous extract from the leaves of Ipomoea staphylina was investigated for its anthelmintic activity against Perionyx excavatus. Methods: Three concentrations (25, 50, 100 mg/ml) of extract were studied in activity, which involved the determination of time of paralysis and time of death of the worms. Piperazine citrate was included as standard reference and normal saline as control. Results: The extract exhibited no anthelmintic activity at all three concentrations. Conclusion: Further study is required on the different solvent extract to evaluate if there is any anthelmintic activity. Keywords: Ipomoea staphylina, anthelmintic, Perionyx excavatus and Piperazine citrate.